2021
DOI: 10.1038/s41598-021-02192-4
|View full text |Cite
|
Sign up to set email alerts
|

Palaeohistology reveals a slow pace of life for the dwarfed Sicilian elephant

Abstract: The 1-m-tall dwarf elephant Palaeoloxodon falconeri from the Pleistocene of Sicily (Italy) is an extreme example of insular dwarfism and epitomizes the Island Rule. Based on scaling of life-history (LH) traits with body mass, P. falconeri is widely considered to be ‘r-selected’ by truncation of the growth period, associated with an early onset of reproduction and an abbreviated lifespan. These conjectures are, however, at odds with predictions from LH models for adaptive shifts in body size on islands. To sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…This species was observed to have a fast life history as the age distribution of its fossil assemblage was skewed to calves and immature individuals [83]. Nevertheless, a histological study suggested that this pygmy elephant had a much slower growth rate than its mainland relatives, and sexual maturity was within the range of extant elephants [84], thus this contradiction requires a further synthetic study on this species. The differences in the life history response among Mediterranean mammals, however, are unsurprising, given that these Mediterranean islands were much bigger than those for which we report life history changes (i.e., the Blakely Island, Kerama Islands, Yakushima Island, Okinawa Island, and Mallorca Island).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This species was observed to have a fast life history as the age distribution of its fossil assemblage was skewed to calves and immature individuals [83]. Nevertheless, a histological study suggested that this pygmy elephant had a much slower growth rate than its mainland relatives, and sexual maturity was within the range of extant elephants [84], thus this contradiction requires a further synthetic study on this species. The differences in the life history response among Mediterranean mammals, however, are unsurprising, given that these Mediterranean islands were much bigger than those for which we report life history changes (i.e., the Blakely Island, Kerama Islands, Yakushima Island, Okinawa Island, and Mallorca Island).…”
Section: Discussionmentioning
confidence: 99%
“…✝ Fossil taxa. * Life history of Elephas falconeri was disputed [83, 84]. ** Muntiacus reevesi was an artificially introduced animal in the 1980s.…”
Section: Discussionmentioning
confidence: 99%
“…The commonly held view that tooth morphology represents an evolutionarily conservative trait, that is, that it changes comparatively slowly over the course of evolution (Hillson, 2014;Jordana et al, 2014;Smith, 1989Smith, , 1991Smith, , 2000, is corroborated by our findings with respect to the overall dimensions of the pig M 2 . However, tion (Jordana & Köhler, 2011;Köhler et al, 2021;Köhler & Moyà-Solà, 2009). We consider the selective pressure occurring in the process of pig domestication to have acted in the opposite direction.…”
Section: Linear Enamel Thickness and Ameloblast Secretory Lifespanmentioning
confidence: 99%
“…The analysis of incremental growth marks with known periodicities in dental hard tissues enables the reconstruction of tooth growth and inferences on life‐history traits of extant and fossil species (Dean, 1987 , 2000 , 2006 ; Dean et al, 1993 , 2020 ; Dirks et al, 2009 , 2012 ; FitzGerald, 1998 ; Hogg, 2018 ; Köhler et al, 2021 ; O'Meara et al, 2018 ; Schwartz et al, 2002 , 2006 ; Shellis, 1998 ; Smith et al, 2006 ). In mammalian enamel and dentine, the periodicities of growth marks have been determined by labelling of the forming tissues (Bromage, 1991 ; Bromage et al, 2009 ; Emken et al, 2021 ; Iinuma et al, 2004 ; Kawasaki & Fearnhead, 1975 ; Kierdorf et al, 2013 ; Ohtsuka & Shinoda, 1995 ; Okada & Mimura, 1938 , 1940 ; Papakyrikos et al, 2020 ; Schour & Poncher, 1937 ; Smith, 2006 ; Yilmaz et al, 1977 ).…”
Section: Introductionmentioning
confidence: 99%
“…Paleohistology is a useful tool for elucidating the growth patterns, life history and physiology of extinct vertebrates [20][21][22][23][24][25]. It has provided insights on several aspects of the evolutionary biology of extinct mammals including the reconstruction of their growth and development [22,[26][27][28][29], adaptations to different lifestyles [27], ecology [22,29,30] and physiology [22,27].…”
Section: Introductionmentioning
confidence: 99%